50 states, 5,000 ideas : - Yogerst, Joseph R. (National Geographic, 2017)
Organized state-by-state then province-by-province, 50 States, 5,000 Ideas showcases the best travel experiences in every state and province, from the obvious to the unexpected. Sights include national parks, beaches, hotels, Civil War battlefields, dude ranches, out-of-the-way museums, and the list goes on and on. You'll discover the world's longest yard sale in Tennessee; swamp tours in Louisiana; dinosaur trails in Colorado; America's oldest street in NYC; a string of lighthouses in Nova Scotia; authentic Chinese night markets in British Columbia; and the best spot to watch for sea otters on the central California coast. Each entry provides detailed travel information, as well as fascinating facts about each state, that will help fuel your wanderlust and ensure the best vacation possible